2010
DOI: 10.1117/12.870769
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of defects in plates by two-dimensional ultrasonic displacement maps: comparison between pulsed TV-holography measurements and finite element method predictions

Abstract: Pulsed TV-holography (PTVH) can be used for obtaining two-dimensional maps of instantaneous out-of-plane displacements in plates. In particular, scattering patterns generated by the interaction of elastic waves with defects can be measured with PTVH and employed for non-destructive inspection and damage detection in plate structures. For quantitative characterization of damage (position, dimensions, orientation, etc.) on this basis, modeling of elastic wave scattering is usually performed in terms of full-vect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The visual comparison of the images for the whole set (figure 5) confirms the reasonable agreement between experimental and numerical total fields, both in amplitude, phase and real part, except perhaps for the amplitude in the backscattering zone as we have claimed previously 6,7 . This conclusion was checked now in more detail by considering first the local total error distribution (figure 6).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The visual comparison of the images for the whole set (figure 5) confirms the reasonable agreement between experimental and numerical total fields, both in amplitude, phase and real part, except perhaps for the amplitude in the backscattering zone as we have claimed previously 6,7 . This conclusion was checked now in more detail by considering first the local total error distribution (figure 6).…”
Section: Resultssupporting
confidence: 85%
“…can be extracted by analyzing the features of the associated scattering pattern. We have also shown that the direct problem of the scattering of Rayleigh-Lamb waves by through-thickness defects in plates can be solved by using numerical methods combined with a simplified 2-D scalar model, rendering numerical scattering patterns that by visual comparison show a reasonable agreement with the experiment, both in harmonic and transient regimes, except for the amplitude in the backscattering zone [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations